The Victim’s Perspective : Essays on Moral Responsibility - Leventi, Marianna (2025)
This thesis approaches the moral responsibility debate from the “victim’s perspective,” a perspective that is often neglected in the literature. My aim is to show that by taking the victim’s perspective, philosophical discussions can gain a more spherical if not, complete picture of responsibility practices. The thesis explores the implications of adopting or excluding certain perspectives in philosophical discussions of moral responsibility, especially regarding the relationship between moral responsibility and blame. Specifically, my assumption is that in order to understand blame, and other moral responses, we need to be aware of the situatedness of philosophical inquiry and take a closer look at different social realities. In addition, my claim is that we need to understand that responsibility as a moral and social practice which is fundamentally impacted by structural injustice and philosophers’ situated epistemic standpoint. In the thesis, I investigate from a victim-based point of view, different types of blaming responses such as epistemic blame, victim blaming, and moral protest. My overarching aim in doing so is to highlight how this alternative perspective can make sense of previously uncharted dimensions of the debate. Taking the victim’s perspective into account can help us develop a more complex picture of how we blame and when we blame. The first aspect of blame I am going to look at, epistemic blame, focuses on the awareness or knowledge required for someone to be blameworthy. I will then move on to victim blaming. This is a social phenomenon, but it is also of philosophical phenomenon, because it shows how our blaming responses can be misguided, namely by blaming the victim of an offense instead of the wrongdoer. Finally, I will also look at moral protest as an alternative response to blame. What is important with regard to this issue is that moral protest can be adopted by victims when they are systematically victimized but cannot get out of the harmful relationship. The last paper of the thesis examines what we do after blame responses have been made and it may be time for the process of forgiveness to begin. The discussion of forgiveness is also novel insofar as it focuses on how victims fit into that process
Date: 2025-10-11 Time: 10:15 Place: LUX C121 External reviewer Name: Julia Driver Title: professor Affiliation: University of Texas at Austin
Keywords: moral responsibility; ethics; Victims; forgiveness; moral protest; victim blaming; perspective